'A Supreme Fiction': Michael Fried and Art Criticism. (April 2017) - Green, Alison
One of the striking aspects of the trenchant legacy of Michael Fried's 'Art and Objecthood' is its status as a piece of art criticism. Widely perceived as difficult and personal, philosophical and explicatory, doxa or sermon, the essay stands out. To explore its singularity, this article compares Fried's conception of the period criticism of 18th-century French painting in his book Absorption and Theatricality: Painting and Beholder in the Age of Diderot (1980) and the method of criticism enacted in 'Art and Objecthood' (1967) which he saw as connected. The author pursues this and other crossings between Fried's art historical writings and art criticism, tracking it to an extended endnote in Fried's Menzel's Realism: Art and Embodiment in Nineteenth-Century Berlin (2002). 'Art and Objecthood' is a key essay in this story aimed at Fried's thinking about criticism, its history, theory and practice. Doing this matters because it puts the critic in a particular relation to art and to Fried's idea of an 'ontologically prior relationship between painting and the beholder'.